Library day - Rockwell, Anne F. (My first experience book., 2016)
Author Anne Rockwell celebrates books, the love of reading, and of course, libraries, with a picture book about a child's first visit to the library! One day, a young boy visits the library for the very first time. While he's there he listens to stories, reads books and magazines, and learns that there are also movies, crafts, chess, and puppet shows--something for everyone! With simple, lyrical text and bright illustrations that jump off the page, Library Day brings the joys of reading vividly to life.